Directivity of scanning circular ring antenna - Panko, V. S.; Salomatov, Y. P.; Sugak, M. I. (2015 International Siberian Conference on Control and Communications (SIBCON), 2015)
In this paper scanning mode of circular ring antenna is considered. It is shown that such an antenna possess narrower main beam and larger sidelobe level in comparison with circular aperture of the same radius. Ring antenna directivity does not change while scanning to broadside.